Pengembangan e-modul berbasis contextual teaching and learning (CTL) pada pokok bahasan persamaan dan pertidaksamaan linear satu variabel - Anggraini, Deti; Octaria, Dina; Fitriasari, Putri (Jurnal Pendidik Indonesia, 2023)
This study aims to produce an e-module product based on Contextual Teaching and Learning (CTL) on the subject of valid, practical, and effective single-variable linear equations and inequalities. This research is a type of research and development using the ADDIE model, namely analysis, design, development, implementation, evaluation. The object of research is the quality of e-module based on CTL on the subject of linear one-variable equations and inequalities. Data collection techniques in this study were observation, questionnaires, and tests. The data analysis techniques in this study were validity, practicality, and effectiveness. The results of this study were obtained from aspects of validity, aspects of practicality and aspects of effectiveness. a) the validity aspect obtained valid criteria based on the evaluation of material experts with a total average score of 3.4; media expert with an average score of 3.7; educators with an average score of 3.5 and practicality aspects obtained practical criteria based on student response questionnaires with an average score of 3.2 and the observation results of 82.5%; b) effectiveness aspects with high criteria based on student learning outcomes tests with a percentage of 75.00%.